AI AND EDUCATION: EMPOWERING LEARNERS WHILE SUSTAINING HUMAN-CENTERED VALUES - R.Arslonova (TADQIQOTLAR, 2025)
Abstract:  This  article  explores  the  intricate  relationship  between  artificial intelligence  (AI)  and  education.  It  examines  AI's  potential  to  personalize  learning, enhance inclusivity, and improve educational quality, while also addressing ethical and social  challenges  associated  with  technology  integration.  The  analysis  considers pathways  for  advancing  education  while  preserving  human  dignity,  drawing  on UNESCO's ethical guidelines for AI and the United Nations Sustainable Development Goals (SDGs). Recommendations are proposed for the effective and ethical adoption of AI in education to empower learners and promote equitable access to knowledge.